FINTECH: features of banking business development in Ukraine - Nakonechna, Olena; Mykhailyk, Olga (My University, 2021)
The article implements the current state of the global FinTech market in the banking sector, analyzes the level of FinTech pervasion in foreign markets and identifies trends in modern global investment in FinTech-companies. Research of the banking Ukrainian FinTech-market is made and defined its basic model of cooperation between banks and FinTech-companies. The main factors that contributed to the development of FinTech is: the development of technology and innovation and the search for alternative ways to finance the banking business. The factors that are unique for Ukraine, which in combination with the developed infrastructure contribute to the development of the FinTech-market: infrastructure, legal and regulatory environment, access to capital and investment, qualifications. Potential areas of cooperation between FinTech-companies and banks are: personal finance management, payments, marketplaces (lending), investment platforms, collective financing (crowdfunding), security, B2B FinTech, money transfers, big data analysis (Big Data), regTech, insureTech, artificial intelligence, neobanks (banks-challengers), crypto-currency, blockchain. The risks and opportunities for the banking and consumer sectors related to the implementation of FinTech solutions are outlined. The main trends in FinTech industry development is also identified, which should be taken into account when forming key factors of banking sector transformation to implement the new Ukrainian banking business models and indicated positive factors for the introduction of new financial services and products.
Keywords: фінтех; fintech; банк; bank; фінтех-компанії; FinTech companies; фінансові послуги; financial services; кафедра економіки і права